Theologie en politiek: De discussie over de staat Israël in Kerk en Theologie 1968-1981 - Klinken, G. J. van (Kerk en theologie, 2024)
Interest in the State of Israel soared during the aftermath of the Six Day-War (1967). In Kerk en Theologie, G.C. van Niftrik, A.W. Dekker and A.A. Spijkerboer took their clues from Karl Barth and F.W. Marquardt. The notion of a unique position of Israel in salvation history was however vehemently denied by those who stood up for Palestinians (Kroon, Verkuyl, Slomp, Snoek, others). Some major agents in Dutch Protestantism remained at the sidelines: especially Calvinist Orthodoxy and the Evangelicals. Their interest in the Jewish people cannot be doubted, but is hardly reflected in the pages of Kerk en Theologie.